2013
DOI: 10.1590/s2317-15372013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Performance of soybean plants as function of seed size: II. Nutritional stress

Abstract: The high quality seed is an input with invaluable for obtaining soybean crops with higher yields; for it reflects the results of high investments in research of modern technologies, which will be converted into high productivity levels. Thus, the aim of this study was assessing performance of soybean seeds, sorted by size, and grown in soils with different phosphorus levels. To this, seeds of two soybean cultivars (MSoy 9144RR and MSoy 8527RR) were sorted with aid of circular screens with perforations of 5.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…If the raw materials are limited, the process can not perform normally. The grain size decreases when soybean grown in a soil with low fertility, especially in low phosphorus (Soares et al, 2013). Presumably, phosphorus in Entisols-Inceptisols was lower than Vertisols because soil parent material of Entisols-Inceptisols in Jambegede Research Station is originated from volcanic material.…”
Section: Discussionmentioning
confidence: 99%
“…If the raw materials are limited, the process can not perform normally. The grain size decreases when soybean grown in a soil with low fertility, especially in low phosphorus (Soares et al, 2013). Presumably, phosphorus in Entisols-Inceptisols was lower than Vertisols because soil parent material of Entisols-Inceptisols in Jambegede Research Station is originated from volcanic material.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate availability of light, temperature, water and nutrients during the period of performance determination, between the start of the pod formation (R3) and full green grain (R6) guarantees a high number of grains per plant [48,50,51,52,53]. It should be remembered that the plasticity in the number of grains per pod in soybeans is very low between 2.1-2.5 seed/pod [54,55,56], same with different cultural practices [57,58,59]. Thus, the number of grains per pod of soybeans can be less sensitive to stress compared to the number of pods.…”
Section: Yield Component Basismentioning
confidence: 99%
“…The reduction in the number of branches observed in sensible cultivars under high competition among plants promoted by the higher CO 2 concentration can inhibit the axillary buds ontogeny in early vegetative stages [34,55]. There is a need for further studies to elucidate the mechanisms of inhibition of branch ontogeny, and how early foliar self-shading can influence the ontogeny of branches and the number of its internodes.…”
Section: Changes In Plant Height Branches and Racemesmentioning
confidence: 99%
“…However, some studies have reported divergent results, in which the influence of seed size on yield components (SOARES et al, 2013), seed oil and protein content, and productivity was observed (MOURTZINIS et al, 2015).…”
Section: Introductionmentioning
confidence: 99%